KINERJA KEUANGAN INSTANSI PEMERINTAH DAERAH DAN KONSEP VALUE FOR MONEY: KINERJA KEUANGAN INSTANSI PEMERINTAH DAERAH DAN KONSEP VALUE FOR MONEY - Bahri, Dimas Samsul; Mawikere, Lidia M; Maradesa, Djeini (GOING CONCERN : JURNAL RISET AKUNTANSI, 2024)
The assessment of public sector organizations is not based solely on the outputs produced. Instead, a more comprehensive assessment requires simultaneous consideration of inputs, outputs and outcomes. It is even necessary to include measures of service distribution and coverage (equity and service coverage) into the assessment process. The purpose of this research is to analyse the measurement of government financial performance using the concept of value for money, with a particular focus on the economic, efficiency and effectiveness ratios at the Manado City National and Political Unity Agency or known as KESBANGPOL. This is a qualitative research design with a descriptive approach. The data source used is primary data and secondary data collected through observation, interviews, and documentation. The results showed that the financial performane of the Manado City Kesbangpol Agency had not met the criteria measured dy economic, efficiency, and effectiveness ratios. Additionally, the financial performance did not meet the criteria of ‘very effective’ due to the failure to achieve the set budget target. The research findings indicate a discrepancy between the budget and target, which is attributed to the existence of activities that are budgeted but not implimented. Keywords: Economist, Effective, Effisience, Financial Performance, Value For Money